Development of an asymmetric re-centering dissipative device. (October 2019) - Morelli, Francesco; Piscini, Andrea; Salvatore, Walter
Abstract: The seismic retrofit design of structures in which the bracings are compressed due to the presence of significant vertical loads shall take into account the strong asymmetric working conditions of the bracings induced by the seismic action. The initial compression and the consequent asymmetric cyclic loading lead, indeed, to poor global performances and drawbacks in the case of seismic retrofitting through the substitution of the existing bracings with dissipative ones. In order to overcome such issues, this paper presents the development of an asymmetric re-centering dissipative device characterized by a different behavior in tension and in compression and by a strong re-centering capacity, making it suitable to resist and dissipate the energy generated by asymmetric cyclic loadings. The paper firstly analyzes the specific issues of structures in which the bracings work in strong asymmetric loading conditions due to the presence of significant vertical loads, highlighting the main problems that can arise adopting traditional dissipative bracings. Then the proposed device is conceptually described and its behavior experimentally assessed. Finally, the structural behavior of a sub-system equipped with the proposed device is assessed through numerical analyses. The experimental and numerical results show the effectiveness of the proposed device in reducing the residual displacements and protecting the other structural elements demanded to resist to the vertical loads. Highlights: The development of a new re-centering device with asymmetric hysteretic behavior is presented. The situations in which the proposed device is useful are analyzed in the paper. The experimental results testifies the asymmetric and re-centering behavior of the proposed device. The numerical simulations highlights the possibility of overcoming some of the drawbacks of classical dissipative devices.